Global Adoption of Telepharmacy: Challenges, Opportunities, and Implementation Strategies (Asian Journal of Pharmaceutics (AJP), 2026)
Telepharmacy, a rapidly evolving telehealth application, has the potential to revolutionize healthcare delivery by providing remote pharmaceutical services, improving access to care, and addressing healthcare disparities. This review examines the global adoption of telepharmacy, focusing on the challenges, opportunities, and implementation strategies across various countries. While developed nations such as the United States, Canada, Australia, and the United Kingdom have successfully integrated telepharmacy into their healthcare systems, low- and middle-income countries (LMICs) face significant barriers to adoption. These obstacles include inadequate technological infrastructure, a lack of regulatory frameworks, financial constraints, workforce limitations, and cultural resistance. The COVID-19 pandemic has accelerated the adoption of telepharmacy worldwide, highlighting its potential to ensure the continuity of care and improve patient outcomes. However, the implementation of telepharmacy in LMICs remains hindered by digital literacy gaps, data privacy concerns, and limited awareness among health care professionals and the public. In Saudi Arabia, the adoption of telepharmacy is gaining momentum; however, challenges persist, including the need for comprehensive regulatory structures, technological advancements, and cultural acceptance. To fully harness the benefits of telepharmacy, policymakers, healthcare organizations, and technology providers must collaborate to establish supportive regulations, invest in digital infrastructure, provide training for healthcare professionals, and promote public awareness. By leveraging the lessons learned from successful telepharmacy models and addressing context-specific challenges, countries can optimize the delivery of pharmaceutical care, improve medication adherence, and enhance patient outcomes in the digital era.